(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص: قبيلة زناتة من أكبر القبائل البربرية في المغرب الأوسط تتميز باتساع موقعها الجغرافي وتعدد بطونها الأمر الذي دفعها لممارسة النشاط التجاري وكما هو واضح للعيان أنّ هذا النشاط يعتمد على نظم حتى تكتمل العمليات التجارية، ومن خلال البحث في كتاب "الإحكام لمسائل الأحكام" لأبي علي الزناتي يمكننا أن نستشف هذه النظم التي بدورها تمكننا من رسم صورة لنظم التسعير وعمليات البيوع في الفترة الوسيطة وكذلك العوامل المؤدية لارتفاع الأسعار وانخفاضها في فترة قيد الدراسة، كما يعرج المؤلف لجانب مهم من جوانب النظم التجارية الزناتية وذلك بتسليطه الضوء على أنواع البيوع الموجودة في الأسواق الزناتية، والتي قسمناها لبيوع جائزة مشروعة وبيوع احتكمت للعرف القبلي أكثر من الجانب الشرعي فاصطلحنا عليها بالبيوع المحرمة. خلصت الدراسة أن الأسعار والبيوع من أهم النظم التجارية الزناتية لذلك لا يمكن دراسة البيوع دون التطرق لنظام التسعير كما كان لهذا الأخير تأثير على عمليات البيع. الكلمات الدالة: زناتة، المغرب الأوسط، الأسعار، البيوع. Abstract: Znata tribe is one of the largest Berber tribes in the Central Maghreb. It is characterized by its wide geographical location and its multiple ascendants, which led it to practice commercial activities. And as it is clearly seen, this activity depends on particular systems for the commercial operations to be completed. With the search through the book "The succinctness of the rulings matters" by Abi Ali Al-Zanati, we can distinguish these systems that, in turn, enable us to draw a picture of pricing systems and sales operations in that period, as well as the factors leading to high and low prices back then. Moreover, the author laments an important aspect of the commercial and pricing systems in Znata markets, which were divided into two main categories: legitimate sales, and the sales that followed tribal norms, which were entitled in this study as illegitimate sales. The study led to the conclusion that prices and sales are among the most important commercial systems of Znata, therefore it is not possible to study sales without tackling the pricing system, as the latter had an effect on sales operations. Key words:Znata, Central Maghreb, Prices, Sales.